Violent Crime in the Lives of Homeless Female Ex-Offenders. (1st February 2017) - Nyamathi, Adeline M.; Salem, Benissa E.; Hall, Elizabeth; Oleskowicz, Tanya; Ekstrand, Maria; Yadav, Kartik; Toyama, Joy; Turner, Susan; Faucette, Mark
Abstract : The cyclical pattern of violence in the lives of homeless female ex-offenders may precipitate ongoing substance use and recidivism; all of which have shown to be mounting public health issues affecting successful reentry. This paper, which analyzed baseline data from a longitudinal study of 126 female ex-offenders in Los Angeles and Pomona, California, highlighted the factors found to be associated with violent crime among homeless female ex-offenders. A multiple logistic regression model for whether or not the last conviction was for a violent offense indicated that poor housing ( p = .011) and self-reported anger or hostility ( p < .001) were significant correlates. An ordinal regression model for the number of violent offenses also indicated that affectionate support was associated with committing fewer number of violent crimes ( p = .001), while positive social interactions ( p = .007), and anger/hostility ( p = .015) were associated with greater number of violent crimes. Implications for developing a comprehensive array of strategies that can mitigate the pattern of violence often seen in the lives of homeless female who have recently exited jails and prisons is discussed.